A Study of Exposure of Overall Background Radiation In Syangja District of Nepal - Timilsina, S.; Poudel, K. R.; Poudel, P. R. (Himalayan Physics, 2017)
Correction: On 14th August 2023 the initial of the first author was changed from 'T' to 'S' in order to match the information on the PDF. This study presents general exposure of background radiation to the people living or visiting nine places of Syangja district. A portable GM counter was used to quantify the total radiation at those places. The findings of this study show variation of radiation level at different places. Comparatively large values of radiation counts are observed at high altitude places (Gurung Dada: 70.23 cpm and Pokhari Dada: 64.77 cpm). The value of radiation count inside room is comparatively larger than that at outside room for these places. Moreover, small value of radiation count is observed at river side (Bank of Aandhikhola river: 21.63 cpm). Little large values are observed near Saligram stones and ancient statue than at other regions of one historical/religious place. Hence, results show fluctuations of background radiation level for different places. Some places have comparatively large value of radiation count while some places have comparatively small value. But there is no any abnormal value of radiation counts for all sample places. So there is, generally, no significant risk of public exposure to the background radiation for sample places. The Himalayan Physics Vol. 6 & 7, April 2017 (92-95)